"AFTER THE EVENT": FREUD'S UNCANNY AND THE ANXIETY OF ORIGINS. (October 2015) - BARNABY, ANDREW
<x xml:space="preserve">Abstract</x> This essay aims to revise Freud's theory of the uncanny by rereading his own essay of that name along with the key material Freud drew on in formulating his theory: E. T. A. Hoffmann's short story "The Sandman" (1816a) and Ernst Jentsch's essay "On the Psychology of the Uncanny" (1906a). While arguing, initially, both that Jentsch's work is fundamentally misconstrued by Freud and that it offers a better account of what happens in Hoffmann's story, the essay moves beyond Jentsch's account to offer a more philosophically oriented theory of the uncanny, one more in line with Freud's ideas in Beyond the Pleasure Principle (1920a).